Clinical Studies with Topical Fluocinolone Acetonide in the Treatment of Various Dermatoses - Kanee, Ben (1963)
Fluocinolone acetonide cream is a new, potent topical corticosteroid. When used in conjunction with an occlusive plastic film dressing, herein described, it is highly effective in the treatment of psoriasis of the glabrous skin, pustular and paronychial psoriasis, neurodermatitis, and lichen planus. Psoriasis of the intertriginous areas responds to the local use of the fluocinolone cream alone. Relapses on cessation of treatment respond as a rule to retreatment. Indications, limitations, reactions and contraindications to this form of treatment are discussed.